Optimization of a cylindrical thermomagnetic engine for power generation from low‐temperature heat sources. (12th January 2021) - Ahmed, Rahate; Park, Jin Chul; Zeeshan,; Mehmood, Muhammad Uzair; Lim, Sang Hoon; Lee, Jaeyoung; Chun, Wongee
Summary: A low‐grade heat source can be used as an operating fuel to run a thermomagnetic heat engine (TME), whose performance is determined by the interaction of the magnetic field between a permanent magnet and a thermomagnetic material used in the engine. In this paper, we present a cylindrical TME to scavenge low‐grade thermal energy and its eventual conversion into mechanical energy. Various models were investigated to optimal performance via COMSOL Multiphysics 5.4, especially in terms of axial torque generation, where experimental validations were made as appropriate. Finally, an optimized model was selected to develop a prototype of the TME. Using hot and cold water at a temperature of 65°C and 22.5°C, the TME produced an average torque and mechanical power of 81.73 N mm and 1.17 W, respectively. The thermal to mechanical conversion efficiency was calculated to be 0.104%. The present mathematical model can be effectively used to design and fabricate a commercially applicable TME in reality, and this, in turn, will allow for the development of a practicable and efficient TME for the exploitation of low‐grade thermal energy. Abstract : A novel design of a cylindrical thermomagnetic engine (TME) was proposed to scavenge low‐grade thermal energy. The permanent magnet, and water flow angle was optimized using the COMSOL Multiphysics software. The simulation results identified the optimal shape and size of the permanent magnet for enhancing the efficiency of a TME. At a temperature difference of 42.5°C, the thermal efficiency of the TME was calculated at 0.104%.